Removal of Congo Red Dye From Aqueous Solution Using Eco-Friendly Adsorbent of Nanosilica (Baghdad Science Journal, 2021)
The development of a new, cheap, efficient, and ecofriendly adsorbents has become an important demand for the treatment of waste water, so nano silica is considered a good choice. A sample of nanosilica (NS) was prepared from sodium silicate as precursor and the nonionic surfactant Tween 20 as a template. The prepared sample was characterized using various characterization techniques such as FT-IR, AFM, SEM and EDX analysis. The spectrum of FTIR confirms the presence of silica in the sample, while SEM analysis of sample shows nanostructures with pore ranging (2-100nm).The adsorptive properties of this sample were studied by removing Congo red dye (CR) from aqueous solution. Batch experimental methods were carried out at room temperature (25⁰C) to study the different variables which affect the adsorption process like: NS amount, initial concentration of CR, and contact time. The results were 0.2 g of NS/50 ml of dye solution and 60 min contact time to reach equilibrium. The experimental results at equilibrium were analyzed using Langmuir and Freundlich adsorption isotherms and showed the best fitted with Freundlich model which reveal heterogeneity of the surface of NS adsorbent. Kinetics aspects were also investigated by evaluating parameters from pseudo- first and pseudo-second order reaction equations on adsorption rate which show good fitting with both kinetics equations, but pseudo-second order equation was the best to describe the kinetics parameters.The adsorptive properties of this sample were studied by removing Congo red dye (CR) from aqueous solution. Batch Experimental methods were carried out at room temperature (25⁰C) to study the different variables which affect the adsorption process like: NS amount, initial concentration of CR, and contact time. The experimental results at equilibrium were analyzed using Langmuir and Freundlich adsorption isotherms and show best fitted with Freundlich model which reveal heterogeneity of the surface of NS adsorbent. Kinetics aspects was also investigated by evaluating parameters from pseudo- first and pseudo-second order reaction equations on adsorption rate which show good fitting with both kinetics equations, but pseudo-second order equation was the best to describe the kinetics parameters.